The matrimonial culture in Cairo's upper middle class: Capital, collective and consumption - Al-Mokadem, Mariam (AUC Knowledge Fountain, 2020)
This thesis focuses on discourses and practices relating to the journey to matrimony in Cairo's upper middle class. In other words, I will focus on how members of this social class communicate and perform their beliefs about matrimony. It is a journey to matrimony in Cairo's upper-middle class, with reference to the temporalities a bride undergoes in order to actualize the new ordinary of marriage through suitor selection, matrimonial practices, and consumption patterns. I will investigate the basis on which a bride selects her suitor and the extent to which a bride and groom involve their parents (and in-group members) in the suitor selection process. I will also examine the practices in which families engage to get acquainted with one another, with reference to the social and cultural meanings of such practices. I will additionally inspect the ways in which marriage deals are made, especially in terms of the allocation of matrimonial transactions, and the extent to which the collective plays a major role in the pre-material acquisition process, that is, matrimonial consumption patterns. I worked as an intern at an interior designer firm in Heliopolis, Cairo, where I met seven couples in the pre-marital material acquisition phase. My ethnographic toolkit is based primarily on un-structured interviews with the brides, supported by observation notes of the preliminary meeting with the interior designer, the bridal home furnishings, and the kitchen utensils shopping. Through this ethnography of the particular, I was able to observe that members of the same social class react differently to matrimony; due to their subjective life experiences. I classified the reactions to matrimony into three typologies. However, none of the nuances undermine the logic of the habitus as class motivated. The different reactions to matrimony show the way through which individuals create a sense of individuality in relation to the structuring structures into which they were born and raised. The couples seem to constitute their identities through the process of hailing in social interactions. In other words, the typologies suggested in this research show that none of the couples initiated a radical change, but, rather, engaged in adaptive strategies.